The importance of Pap smear during pregnancy: an integrative review (Research, Society and Development, 2020)
The objectives of this study were: to identify the importance of having a Papanicolaou test during pregnancy; to verify the factors that lead women to not want to have Papanicolaou test during pregnancy; and identify the role of nurses regarding Papanicolaou test during prenatal care. It is an integrative literature review, searching for articles in the databases: Medical Literature Analysis and Retrieval System Online (MEDLINE), Latin American and Caribbean Literature in Health Sciences (LILACS) and Database Nursing data (BDENF). A time frame of the last 10 years was used in all searches. The search terms were "Papanicolau", "Gestação" and "Pré-natal". After applying the inclusion and exclusion criteria, five articles were selected that comprised the sample and two themes were obtained: Knowledge of pregnant women about the importance of Papanicolaou test for the prevention of cervical cancer during prenatal care and Proper preparation and the approach of nurses about the Papanicolaou test in pregnant women. It was possible to identify that pregnancy is an excellent opportunity for Papanicolaou test, because it is part of the prenatal routine and the nurse must be prepared and qualified to provide educational and preventive orientations and information about the exam to these women.